The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1464-410x.2005.05880.x
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study of renal cell carcinoma and prostate cancer in the same patients

Abstract: OBJECTIVETo investigate the incidence of prostate cancer in men with renal cell carcinoma (RCC) and the incidence of RCC in men with prostate cancer. METHODSWe evaluated the database of the Surveillance, Epidemiology and End Results Program of the National Cancer Institute from 1973 to 1996, to calculate the incidence of RCC in men with prostate cancer and the incidence of prostate cancer in men with RCC. The standardized incidence ratio (SIR, observed/expected) was calculated for each of the scenarios of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
(9 reference statements)
0
8
0
3
Order By: Relevance
“…Interestingly, our data showed that pathways related to renal cell carcinoma (RCC) were significantly upregulated upon hypoxia treatment of prostate cancer cells. Previous clinical studies have shown that men with prostate cancer have a significantly higher chance of developing RCC ( 37 ). Accordingly, our analysis showed that hypoxia microenvironment in prostate cancer cells significantly upregulated MET and ETS1 to activate key cell proliferation signaling cascades that are important for RCC while upregulating GLUT1 and VEGF to increase nutrient availability, potentially promoting the subsequent development of RCC in prostate cancer patients ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our data showed that pathways related to renal cell carcinoma (RCC) were significantly upregulated upon hypoxia treatment of prostate cancer cells. Previous clinical studies have shown that men with prostate cancer have a significantly higher chance of developing RCC ( 37 ). Accordingly, our analysis showed that hypoxia microenvironment in prostate cancer cells significantly upregulated MET and ETS1 to activate key cell proliferation signaling cascades that are important for RCC while upregulating GLUT1 and VEGF to increase nutrient availability, potentially promoting the subsequent development of RCC in prostate cancer patients ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…The finding that increased detection of prostate cancer did not translate into improved cancer‐specific outcomes may be considered worrisome and potentially reinforce policymakers against screening for prostate cancer. As such, whilst these findings have been reported before , these questions have never been as significant as they are now, in the ‘Obamacare’ era.…”
Section: Re: a Comparison Of Prostate Cancer Diagnosis In Patients Rementioning
confidence: 60%
“…Таким образом, в нашем исследовании установлено, что у больных полинеоплазиями с поражением щитовидной железы более высокий, чем в популяции, RR развития других злокачественных новообразований. Так, у женщин, больных раком щитовидной железы, высокий RR синхронного и метахронного развития меланомы (20,6 и 17,1 соответственно), злокачественных новообразований почки (46,3 и 18,5), шейки матки (13,1 и 15,8), молочной железы (11,0 и 11,5) и кожи (8,5 и 9,5 соответственно), метахронного развития лимфом (31,7), рака лёгких и бронхов (18,8), ободочной кишки (16,7), тела матки (11,8), а также синхронного развития рака пищевода (17,8). У мужчин высокий RR синхронного и метахронного развития лимфом (12,8 и 41,8 соответственно), рака почки (33,8 и 55,6) и предстательной железы (24,4 и 35,7), синхронного развития рака пищевода (19,4) и прямой кишки (19,0).…”
Section: выводunclassified
“…Так же, как и в настоящей работе, независимые группы учёных не выявили увеличения риска развития карцином щитовидной железы у больных раком предстательной железы [8,14].…”
Section: выводunclassified
See 1 more Smart Citation